Implementasi Manajemen Risiko Untuk Kredit Macet Konsumtif Di Bank Mandiri Kantor Cabang Jakarta Mampang Prapatan - Hardiyati Kartini Hasibuan; Ai Annisa Utami; Khoirul Umam (RELASI : JURNAL EKONOMI, 2019)
The rapid development of the banking industry with the increasing complexity of bank business activities and increasing credit exposure, will accelerate rapidly. The bank collects funds from additional funds and distributes funds in the form of loans or funds to the people in need, both for working capital and consumption investments. Increasingly tight competition also occurs between banks with each other. Among them by issuing or launching financial services products with various types and interest rates. This research is a qualitative research by following a study conducted over a period of 1 year, describing the risk management process carried out by one of the branches of Bank Mandiri in Mampang Prapatan Jakarta, a method of data collection conducted through observation, interviews, and comparative studies of respondents who comprise from 4 people who included employees from Micro Banking Managers, Micro Credit Analysts, Micro Credit Sales, and sub-branch managers. The sampling technique used is purposive sampling. The results of the research that show the risks involved in the Micro Bank Mandiri Branch Mampang Prapatan have implemented risk management in accordance with BI regulations No.11 / 25 / PBI / 2009 and regulations made by the Directors of PT. Bank Mandiri, called the KPKD or Credit Policy. However, the application of risk management has not been carried out maximally.